Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Solve:
3 + 2 + 52 × 6 − 3 =

(3 + 2) + 52 × (6 − 3) =


Sagot :

Answer:

314 and 161

just use bidmas

1. 3 + 2 + 52 * 6 - 3. *****For both of these questions, we will use BEDMAS = Brackets, Exponents, Division, Multiplication, Addition, Subtraction

3 + 2 + 52 * 6 - 3
= 3 + 2 + 312 - 3
= 314

So, the answer to this question is: 314.

2. (3 + 2) + 52 * (6 - 3)
= 5 + 52 * 3
= 5 + 156
= 161

So, in conclusion, the answer to this problem is: 161.